Pengaruh Disiplin Kerja terhadap Kinerja Kerja di Daima Hotel Padang - Deva Amanda Novresia; Hijriyantomi Suyuthie (Jurnal Bintang Manajemen, 2024)
The research purposes is to calculate how much impact discipline of work has on performance of employee at the Daima Hotel. The population used is all Daima Hotel employees. The research sample utilized was 67 employees. The type of method in this research uses causal associative quantitative. Data was obtained by give questionnaires to informants. The employee work discipline results are sufficient (65.68%). Employee performance is adequate (67.17%). The influence of the two variables is 9.5%.